2017
DOI: 10.1007/s10792-017-0521-7
|View full text |Cite
|
Sign up to set email alerts
|

Herpes zoster keratitis development after acute retinal necrosis

Abstract: This case report describes the unusual development of herpes zoster keratitis after the development of unilateral acute retinal necrosis (ARN) in a patient on antiviral treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Immunohistochemistry was negative for HSV, suggesting that the orbital findings are part of a reactionary inflammatory response. There has been some discussion that ARN may represent a reactivation of a herpetic virus from the ciliary ganglion, 12 , 13 which lies in close proximity to the globe; reactivation of the virus there could serve as the nidus for an orbital inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry was negative for HSV, suggesting that the orbital findings are part of a reactionary inflammatory response. There has been some discussion that ARN may represent a reactivation of a herpetic virus from the ciliary ganglion, 12 , 13 which lies in close proximity to the globe; reactivation of the virus there could serve as the nidus for an orbital inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Dong et al [ 91 ], identified trauma to be the main cause of infectious keratitis in their study[ 91 ]. HSK may also complicate the course of acute retinal necrosis in 20% of sufferers[ 92 - 93 ].…”
Section: Understanding the Pathogenesis Of Herpes Simplex Keratitismentioning
confidence: 99%